2009
DOI: 10.1016/j.juro.2009.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Urethral Stricture Disease in the 21st Century

Abstract: Of strictures treated with urethroplasty today iatrogenic causes account for about half of the urethral stricture cases in the developed world. In about 1 of 3 cases no obvious cause could be identified. The etiology is significantly different in younger vs older patients and among stricture sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
249
3
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(287 citation statements)
references
References 15 publications
10
249
3
25
Order By: Relevance
“…89 Patients with strictures most commonly present with a weak stream, with or without lower urinary tract symptoms. A dilatation of the urethra proximal to the stricture can be observed upon physical examination.…”
Section: Urethral Stricturementioning
confidence: 99%
“…89 Patients with strictures most commonly present with a weak stream, with or without lower urinary tract symptoms. A dilatation of the urethra proximal to the stricture can be observed upon physical examination.…”
Section: Urethral Stricturementioning
confidence: 99%
“…In Europe, Lumen N et al [5] and Palminteri et al [6] reported higher rates of anterior urethral stricture respectively 60.9% and 77.4%. The stricture of the anterior urethra as well as the urethral stricture in general is a pathology of young adult.…”
Section: Discussionmentioning
confidence: 97%
“…7 In the developed world, the aetiology of urethral stricture is mainly iatrogenic, such as transurethral resection, urethral catheterization, cystoscopy, prostatectomy, brachytherapy, hypospadias surgery and idiopathic. 8,9 However in resource poor countries, we still see the pattern of infection and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the dorsal onlay group two of 40 (5%) men developed restricture after a follow-up of 15 (6-24) months, whereas in the buccal mucosa group four of seven required surgical revision for stricture recurrence at 11 (6)(7)(8)(9)(10)(11)(12)(13)(14) months.…”
mentioning
confidence: 99%